2022
DOI: 10.3389/fpsyg.2022.902516
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Evaluation Index System for Training Quality of High-Level Tennis Team

Abstract: The paper established the evaluation index system of training quality of high-level tennis team, which comprising five first-class indexes: work planning evaluation index (i = 4) includes realistic state diagnosis, training goal establishment, specific training content, and training plan formulation; work implementation evaluation index (i = 4) includes training guarantee conditions, training plan implementation, training process monitoring, and training plan adjustment; work monitoring evaluation index (i = 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A higher value of the authority coefficient signifies a higher level of expert authority. Typically, an authority coefficient value of � 0.70 is regarded as indicating a high degree of authority [42]. The survey data from this study revealed that the authority coefficients for the first and second rounds of the questionnaire were 0.86 and 0.89, respectively, indicating that the selected experts in this research possess a high degree of authority (see the S2 Appendix).…”
Section: Plos Onementioning
confidence: 75%
“…A higher value of the authority coefficient signifies a higher level of expert authority. Typically, an authority coefficient value of � 0.70 is regarded as indicating a high degree of authority [42]. The survey data from this study revealed that the authority coefficients for the first and second rounds of the questionnaire were 0.86 and 0.89, respectively, indicating that the selected experts in this research possess a high degree of authority (see the S2 Appendix).…”
Section: Plos Onementioning
confidence: 75%